PEMBERDAYAAN MASYARAKAT DALAM PENANGANAN STUNTING MELALUI PEMANFAATAN PANGAN LOKAL - Festy Mahanani M; Indah Rahayu; Maylia; Wahyu Riniasih; Anita Lufianti; Anggita Septyani Permatasari (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2024)
Background:. Stunting is a condition of failure to grow and develop in babies (0-11 months) and toddlers (12-59 months) who experience chronic malnutrition, especially in the first 1000 days of life, which can be characterized by height that is not appropriate for their age (Arnita et al., 2020 in Panigoro 2020). Stunting is one of the nutritional problems in children globally, and around 161 million children under five in the world are stunted, of which half of the number of stunted children live in the Asian region (Valeriani et al. 2022). Children who experience stunting can be characterized by the height or length of the child being less than -2 SD based on the Z-Score table (Damanik et al., 2021 in Panigoro 2020).Method: Activities are carried out by providing empowerment to the community to be active in local food processing in the context of stunting prevalenceResults: Providing community empowerment related to local food processing can improve children's nutrition in Ngrandah village and the community has added value to local potential advantagesConclusion: From these efforts, we chose to carry out a stunting management program by using local food with a source of vegetable protein in the form of processed tempeh. We chose this because it was considered more affordable and could be practiced by mothers of toddlers, the preparation was in the form of tempeh nuggets. The choice of this program was because from the data we obtained there were still many children experiencing stunting. The first activity we carried out was to survey several hamlets in Ngrandah Village and collaborate with the Village Midwife in searching for data which was also assisted by Posyandu cadres and local food security was maintained.